In vitro prebiotic activity of inulin-rich carbohydrates extracted from Jerusalem artichoke (Helianthus tuberosus L.) tubers at different storage times by Lactobacillus paracasei - Rubel, Irene Albertina (2014)
In the present work the in vitro prebiotic activity of inulin-rich carbohydrates using Lactobacillus paracasei as probiotic microorganism was determined. With this purpose, inulin-rich carbohydrates samples from Jerusalem artichoke tubers stored at 4–5 °C during different times along an overall period of 8 months were extracted.Extraction yield, inulin content and average polymerization degree of inulin-rich carbohydrates samples were also determined. For all samples, extraction yield and inulin content decreased with storage time. In particular, inulin content exhibited values within the range of commercial food grade inulin (≥85%). Average polymerization degree values decreased with storage time ranging from 12.1 to 8.3. The in vitro prebiotic activity of inulinrich carbohydrates samples was assessed using a prebiotic activity score which considered the growing ratio relative to glucose of L. paracasei as well as of the enteric bacteria Escherichia coli when such carbohydrates were used as C source. Inulin-rich carbohydrates extracted from tubers cold-stored during 4 months showed the highest prebiotic activity score, even higher than the corresponding to a commercial food grade inulin, indicating that this sample should be used as a prebiotic food ingredient, representing a potential alternative to the available commercial inulin obtained from chicory roots.